Efforts of Madrasah Heads In Improving The Quality of Education - Muhammad Mizan Asrori; Ibrahim (International Journal of Advanced Studies in Educational Management (IJASEM), 2025)
The quality of education is an institutional benchmark for the wider community, for this reason, a madrasa head must improve madrasah programs to improve the quality of education in the institution. The conclusions of the results of this study indicate that: (1) The quality of education comes from the words quality and education. Quality in Arabic is "khasana" which means good, in English quality means quality, quality. In the Big Indonesian Dictionary, quality is a measure of the good or bad of an object, level, or degree (intelligence, intelligence, and so on). In terms of quality is the quality of meeting or exceeding customer expectations. Thus, quality is a level of quality that meets or even exceeds expectations. In the process of seeking quality education here, the head of the madrasa involves existing resources in the madrasa, namely deputy heads of curriculum, deputy heads of student affairs, and also religious teachers. Because seeing the vision of MTs AlMusthofa Grabagan, namely "The realization of madrasa graduates who are superior, cultured, useful and have noble character". (2) Supporting factors, namely: a. Strategic Institution Location b. Average HR Graduates from Religion and PTU (Public Higher Education) c. The community members and parents of students were enthusiastic. The inhibiting factors are a. Inadequate sources of funds at the institution b. Lack of institutional facilities c. Limited technological tools d. Lack of Honor (salary) e. There is a trend of Islamic boarding schools which provide formal school facilities